Evaluation of Material Request Order to Support Sustainable Construction - Susilowati, Fajar; Anggraeni, Nur Nahdiah (Makara Journal of Technology, 2022)
This study was conducted on one of Indonesia’s apartment projects, in which reinforced concrete is the main structure. Based on existing project data, this project experienced a decline in the construction work’s progress, thus reducing the project’s overall progress. This decline occurred because the delivery of concrete reinforcement material was delayed. This study aimed to determine the process of material request order and its relationship with the work implementation, as well as the factors that influenced the delayed arrival of concrete reinforcement material at the project site. The method used in this study was observation and interview. Data were analyzed by comparing the conditions in the field with the standard operating procedure. Analysis results revealed that the material request order process in this project was implemented excellently, and it followed the existing standard operating procedure. However, material request orders were delayed due to several factors, such as an increase in material price, lack of coordination/communication, and weather disturbances. The results of this study can be used to improve a company’s performance in terms of achieving sustainable construction.